Conservation and restoration of Tang White Marble Panlong Stone Lantern at Beiyue Temple - Yukuan Wang; Xiaoming Li; Yameng Liu (Humanities & Social Sciences Communications)
Abstract A large number of cultural relics are of great historical value, but many have been forgotten due to the temple’s neglect for a long time, and their condition has greatly worsened due to the surrounding environment. This research aims to fill the void of tailored conservation techniques on white marble artifacts from the Tang dynasty by concentrating on the preservation and restoration of Tang White Marble Panlong Stone Lantern, a first-class cultural relic. It analyzes the problem using the historical approach and develops the cultural-architectural context first, followed by pathological studies using XRD, XRF, and FTIR spectroscopy. The dominant salts that contributed to the deterioration were found to include soluble salt (SO4 2− concentrations up to 1197.88 ppm), material loss, structural deterioration, and de-bonding. During the restoration stages, photogrammetry techniques and advanced documenting threedimensional scanning were utilized to create comprehensive 3D models, space planning and VZB virtual reconstruction principles were applied for thorough placement, and finally, penetrating reinforcing JS-01 which is composed of polyurethane, SiO2, and TiO2 was utilized for consolidation. After restoration, the model exhibited improved structural integrity, surface stability, and a more stable structure, void of hazardous salt crusts and deposits. The approach presented in this study addresses the preservation of marble artifacts having complex environmental exposure while respecting the existing damage and the need to provide unobtrusive intervention enhances efforts for integrated preventive conservation of stone heritage.